Emerging of laparoscopic metabolic surgery - Lee, Wei-Jei (Annals of Laparoscopic and Endoscopic Surgery, 2017)
Bariatric surgery has proven successful in treating not just obesity but also significantly decreases the overall obese associated morbidities as well as improves the quality of life in severely obese patients (BMI >35 kg/m2) (1,2).